First Report of Meloidogyne enterolobii on Carrot in China - Wang, Y F (Plant disease, 2014)
Carrot (Daucus carota var. sativus) is one of the 10 most economically important vegetable crops in the world. Recently, stunted and yellowing carrots grown on sandy soil in several commercial fields were observed in Dongshan County, Fujian Province, China. Many round to irregular shaped lumps and swellings were present on the surface of tap and fibrous roots, often with secondary roots emerging from the galls on taproots. Severe infection caused short, stubby, forked taproots leading to losses in quality and marketability. Meloidogyne sp. females and egg masses were dissected from the galls. The perineal patterns from 20 females were oval shaped with moderate to high dorsal arches and mostly lacking obvious lateral lines. The second-stage juvenile mean body length (n = 20) was 416 (390 to 461) μm; lateral lips were large and triangular in face view; tail was thin and length was averaged 56.1 (49.8 to 62.1) μm, with a broad, bluntly rounded tip. These morphological characteristics matched the original description of M. enterolobii (5). Species identity was further explored by sequencing the mitochondrial DNA (mtDNA) region between COII and the lRNA genes using primers C2F3/MRH106 (GGTCAATGTTCAGAAATTTGTGG/AATTTCTAAAGACTTTTCTTA GT) (4). A DNA fragment of ~840 bp was obtained and the sequence (GenBank Accession No. KJ146864) was compared with those in GenBank using BLAST and was 100% identical to the sequences of M. enterolobii and M. mayaguensis, a synonym of M. enterolobii (4). Part of the rDNA spanning ITS1, 5.8S gene, ITS2 was amplified with primers V5367/26S (TTGATTACGTCCCTGCCCTTT/TTTCACTCGCCGTTACTAAGG) (3), and the sequence obtained (KJ146863) was 99 to 100% identical to sequences of M. enterolobii (KF418369.1, KF418370.1, JX024149.1, and JQ082448.1). For further confirmation, M. enterolobii specific primers Me-F/Me-R (AACTTTTGTGAAAGTGCCGCTG/TCAGTTCAGGCAGGATCAACC) (2) were used for amplification of the rDNA-IGS2 sequences of eight populations of the nematode from three localities. A 200-bp amplification product was produced by each population, whereas no product was amplified from control populations of M. incognita or M. javanica. A single product of ~320 bp was obtained using primers 63VNL/63VTH (GAAATTGCTTTATTGTTACTAAG/TAGCCACAGCAAAATAGTTTTC ) (1) from the mtDNA 63-bp repeat region for these populations, and the sequence (KJ146861) showed 100% identity with sequences of M. enterolobii (AJ421395.1, JF309159.1, and JF309160.1). Therefore, the population of Meloidogyne sp. on carrot was confirmed to be M. enterolobii. This nematode has been reported to infect more than 20 plant species belonging to seven families, including Annonaceae, Cucurbitaceae, Convolvulaceae, Fabaceae, Marantaceae, Myrtaceae, and Solanaceae in China. To our knowledge, this is the first report of infection of carrot by M. enterolobii and the first record of M. enterolobii parasitizing a plant in the family Apiaceae in China. M. enterolobii has been reported in Guangdong and Hainan provinces, China. This is the first report of M. enterolobii in Fujian Province, in southeast China. References: (1) V. C. Blok et al. Nematology 4:773, 2002. (2) H. Long et al. Acta Phytopathol. Sin. 36:109, 2006. (3) T. C. Vrain et al. Fundam. Appl. Nematol. 15:565, 1992. (4) J. Xu et al. Eur. J. Plant Pathol. 110:309, 2004. (5) B. Yang and J. D. Eisenback. J. Nematol. 15:381, 1983